Decreased nitrite levels in erythrocytes of children with β-thalassemia/hemoglobin E - Suvachananonda, Thitiwat; Wankham, Amara; Srihirun, Sirada; Tanratana, Pansakorn; Unchern, Supeenun; Fucharoen, Suthat; Chuansumrit, Ampaiwan; Sirachainan, Nongnuch; Sibmooh, Nathawut (Nitric oxide, 2013)
•Nitric oxide bioavailability was determined in thalassemia.•Severe thalassemia patients have decreased erythrocytic nitrite levels.•Severe thalassemia patients have increased plasma hemoglobin and NO consumption.•The erythrocytic nitrite correlates with plasma hemoglobin and NO consumption.•Decreased NO availability may be associated with hemolysis. Nitrite anion is bioactive nitric oxide (NO) species circulating in blood, and represents the NO bioavailability and endothelial function. In this study, we aimed to investigate the nitrite levels and the correlation with hemolysis and severity in β-thalassemia/hemoglobin E (β-thal/HbE). 38 Children (12.0±1.9years of age) with a diagnosis of mild, moderate and severe β-thalassemia were enrolled in the study. The blood nitrite levels and potential plasma NO consumption were measured by the chemiluminescence method. The nitrite levels in whole blood and erythrocytes of the severe thalassemia subjects were lower than those of the control subjects. At day 7 after transfusion of packed erythrocytes, the nitrite levels in erythrocytes increased. The plasma hemoglobin and NO consumption increased in the severe thalassemia subjects. The nitrite levels in erythrocytes inversely correlated with plasma hemoglobin, lactate dehydrogenase activity, potential NO consumption, and lipid peroxidation. Our studies demonstrate the decreased NO bioavailability in thalassemia, which could result from endothelial dysfunction, the increased potential NO consumption in plasma by cell-free hemoglobin and oxidative stress.